Achieving Self-Sufficient Model Villages for Inclusive Growth: A Case of Ramchandrapur - Singh Mahra, Girijesh; Prakash Mishra, Om; Majani, Linda; Janjic, Aleksandra; Kanyenda, Tiwonge (Journal of Rural Development, 2015)
According to 2011 census, 68.84 per cent of Indians live in about 638,691 villages. However, rural India’s share in total national income is less than 45 per cent. Rural India is characterised by low income levels, poor quality of life and weak human capital base. Although in the post-economic reform period, India has grown economically faster, the performance in reduction of poverty, employment and economic disparity remained dismal. This is due to inability to extract and utilise rural people’s potential through their participation in the government at the local level. The need of the hour is the convergence of all development interventions at the grassroots level which can be possible through effective governance within villages to convert them into Model villages- a concept which was not new but have been neglected in the mirage of worldly development. This paper presents a case study on a successful model village of India- Ramchandrapur (a village in Hyderabad, Andhra Pradesh) and evaluates Ramchandrapur’s unique governance system, which has made Ramchandrapur village a self-sufficient and autonomous village. This village has shown that inclusive growth can be achieved by local people by their combined and honest initiatives. Ultimately, India is a land of villages and India will only prosper if it’s all villages prosper with equal socio-economic and inclusive growth.